#### Answer

$x^2-7x+\dfrac{49}{4}
\Rightarrow\left(
x-\dfrac{7}{2} \right)^2
$

#### Work Step by Step

The third term of a perfect square trinomial is equal to the square of half the coefficient of the middle term. Hence, to complete the square of the given expression $
x^2-7x
,$ the third term must be
\begin{array}{l}\require{cancel}\left(
\dfrac{-7}{2}\right)^2
\\\\=
\dfrac{49}{4}
.\end{array}
Using $a^2\pm2ab+b^2=(a\pm b)^2$, then
\begin{array}{l}\require{cancel}
x^2-7x+\dfrac{49}{4}
\Rightarrow\left(
x-\dfrac{7}{2} \right)^2
.\end{array}